Implementasi Ilmu Agama dalam Membentuk Kepribadian Islami pada Generasi Muda - Aden Sutisna; Restu Buana; Seravinus Reagen Manurung; Ismail Mubarok; Dede Nurzaman (Moral : Jurnal kajian Pendidikan Islam, 2026)
This study employed a qualitative-descriptive approach using a phenomenological paradigm and a library research method. The research examined classical theological texts and contemporary developmental psychology literature through a humanistic and empathetic analytical perspective. Results: The findings indicate that religious knowledge cannot operate mechanically, but rather through an internalization process from knowing to doing. Logically, this implementation is based on three main pillars: (1) the Tauhid pillar, which develops muraqabah awareness (the feeling of being observed by God) as an internal control against deviant behavior; (2) the Sharia pillar, functioning as a means of mental training, concentration enhancement, and impulse control (delayed gratification) amidst digital distortion; and (3) the Akhlak pillar, manifested in ethical digital behavior and social empathy. The primary obstacles to implementation are doctrinal teaching approaches and the crisis of role modeling from the adult environment. Conclusion: This study concludes that implementing religious knowledge through a dialogic-humanistic approach is effective in shaping young individuals with strong mental resilience, high integrity, and the ability to adapt confidently to modernity.